(untitled) (Ta’limning zamonaviy transformatsiyasi, 2024)
This thesis provides an extensive exploration of the transformative potential of integrating literary texts into English language teaching, shedding light on the myriad benefits this pedagogical approach offers to language learners. By synthesizing the research findings of eminent scholars such as Lazar (1993), Maleki (2015), O’Neill (2019), and a spectrum of others, this study illuminates how the incorporation of literature can not only enrich language acquisition but also cultivate cultural sensitivity, nurture critical thinking abilities, and enhance overall student engagement in the learning process. Through a comprehensive review of existing literature and empirical studies, this thesis undertakes a detailed analysis of the profound impact of utilizing literary texts as a pedagogical tool in shaping the English language classroom environment. By delving into the multifaceted advantages of integrating literature in language education, this research aims to contribute valuable insights to educators, policymakers, and curriculum developers seeking to optimize language learning outcomes through innovative pedagogical practices.